+0  
 
0
25
2
avatar

Solve for x: (3x + 12)(x + 4) = (4x^2 + 8x + 8x^2)/(2x).

 Nov 23, 2022
 #1
avatar
0

(3x+12)(x+4)=(

=3x2+12x+12x+12

= 3x2+24x+12

=x2+8x+4

 Nov 24, 2022
 #2
avatar
0

 2x * (3x + 12)(x + 4) = (4x^2 + 8x + 8x^2)


6x^3 + 48x^2 + 96x=12x^2 + 8x


6x^3 + 36x^2  + 88x=0


x [3x^2 + 18x + 44] = 0, solve for x


[3x^2 + 18x + 44] = 0 - use the quadratic formula to get:


x = 0
x = -3 - i sqrt(17/3)
x = -3 + i sqrt(17/3)

 Nov 24, 2022
edited by Guest  Nov 24, 2022

16 Online Users